Pengaruh Work-Life Balance, Loyalitas Kerja Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior Di Grand Mercure Medan Angkasa Hotel - Ferdinansyah, Hendy; Azhmy, Muhammad Fauzan; Nasution, Aulia Arief (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
This research was done in DBD Powder Medan, which was a company engaged in the sale of fast food powder. The purpose of this study was to determined the effected of Brand Image and Product Quality on Brand Loyalty in the mediation of Brand Trust in Depok Bubble Drink users in Medan City. The population were consumers who came and bought the company's products with an average of 3,250 consumers per month, sampling using the Slovin formula so that the number of samples were 100 respondents. Sources of data using primary data and data collection techniques were literature study, observation and questionnaires. Data analysis techniques consist of data quality test, classical assumption test, path analysis and hypothesis testing.Based on the results of the study, it partially shows that brand image has a significant effect on brand loyalty, product quality has a significant effect on brand trust. Meanwhile, brand image has no significant effect on brand trust, and product quality has no significant effect on brand loyalty. Simultaneously showed that brand image, product quality and brand trust together have positive and significant effected on brand loyalty in DBD Powder Medan. The correlation between brand image, product quality and brand trust could be said to be strong on brand loyalty at DBD Powder Medan. While the percentage of the ability of brand image, product quality and brand trust to explained brand loyalty was 36.7% and the others amount of 63.3% could be explained by other variables did not examined such as promotion, price, service and so on.